Factors driving educational quality within the framework of SDG 4 for the 2030 agenda: what do training professionals think the 21st century? - Sanchez-Pastor, Valeria; Villar-Guevara, Miluska; Fernández-Mallma, Israel; Apaza-Cáceres, Jesús Alfredo (Frontiers in Education, 2025)
IntroductionAchieving educational quality has always been an essential pillar for sustainable development, social equity, and the transformation of education systems globally. Educational institutions, especially those responsible for training future professionals, play a strategic role in achieving Sustainable Development Goal 4 (SDG 4) by fostering inclusive and equitable educational processes centered on meaningful learning. Therefore, the objective of this study was to analyze the influence of teachers’ effectiveness and English language acculturation on educational quality, examining the mediating role of disposition learning.MethodsA cross-sectional explanatory study was conducted with the participation of 457 university students. The sample was distributed between women (57.8%) and men (42.2%), with ages ranging from 18 to 37 years (M = 21.87; SD = 3). Data were collected using an online self-report questionnaire and analyzed using PLS-SEM. Internal consistency coefficients showed adequate values and confirmed the internal robustness of each construct.ResultsThe hypotheses were supported, with teachers’ effectiveness and disposition learning found to influence educational quality, while teachers’ effectiveness and English language acculturation influenced disposition learning, with the latter assuming a mediating role. However, the proposed model shows that the direct effect of English language acculturation on educational quality is not statistically significant.DiscussionThis new model suggests a reevaluation of existing models on the topics analyzed, given that it involves emerging variables for higher education. The validated findings of this research provide valuable information for higher education management and leadership seeking to achieve higher levels of educational quality. This model merits special attention in future research, including the exploration of other potential factors and the application of these findings to diverse contexts and cultures.